Stand Up Eight: Adversity, Resilience, and Career Adaptability - (:unkn) unknown (My University, 2022)
This study aims to fill a gap in the literature by examining the relationship between adversity and career adaptability. The objectives of this study are: 1) to better understand the relationship between adversity and career adaptability. 2) to examine whether race, gender, socioeconomic status, or resilience moderate this relationship. 3) to compare career adaptability and resilience. These objectives were addressed in a quantitative analysis of survey results gathered of adults living in the United States who speak English. To test for a curvilinear relationship between adversity and career adaptability, we completed a regression analysis of the data using adversity, squared adversity to predict career adaptability. Individual hierarchical multiple regression analyses were conducted for each of the four proposed moderators- gender, race, socioeconomic status, and resilience to test whether these factors moderate the relationship between adversity and career adaptability. A simple linear regression was completed to analyze the relationship between career adaptability and resilience. This study found that the relationship between adversity and career adaptability is curvilinear with higher levels of career adaptability occurring at moderate levels of adversity and lower levels of career adaptability occurring with the lowest and highest levels of adversity. The suggested moderation of this relationship by gender, socioeconomic status, and resilience was not statistically significant. Race was the only proposed moderator which accounted for a significant proportion of the variance in the relationship. Resilience statistically significantly predicted career adaptability. This study is a quantification of the strength some individuals develop through the experience of overcoming adverse circumstances. The study supports initiatives that look to cultivate a growth mindset following adversity and foster generalized resilience and adaptability within career contexts.
Keywords: Adversity; Career Adaptability; Gender; Race; Resilience; Social Class